The Influence of Tarompa E-Module on Peace-Loving Characters - Husni Sabil; Syahrial; Asrial; Dwi Agus Kurniawan; Rahmat Perdana; Fhadira Insani Putri; Sabila Eka Septi (Jurnal Pendidikan Indonesia, 2023)
Peace-loving character plays an important role in helping children develop a superior personality. E-modules can draw students' attention and making learning enjoyable. This can helping children in develop a superior personality. The purpose of this study was to analyse the use of the Tarompa e-module on students' peace-loving characters and to find out whether there is influence and comparison in the use of the e-module with peace-loving characters in elementary schools. This study used quantitative research by comparing 4 schools with a total of 68 students. This study is use questionnaire instrument. The data analysis technique used is descriptive statistical test and inferential test in the form of assumption and hypothesis testing.The results of this study are that there is a comparison and there is an effect of using the tarompa e-module on the peace-loving character of elementary students. The results of this study can be used as teaching resources to help students learn about the variety of Tarompa local wisdom. The research recommendation is to use an electronic module based on Tarompa local wisdom which can be used to teach other characters.